EFEKTIVITAS PIRIPROKSIFEN DALAM UPAYA PENGENDALIAN NYAMUK AEDES SP SEBAGAI VEKTOR DEMAM BERDARAH DENGUE: SEBUAH TINJAUAN NARATIF - Dharma, Fitri Yeni; Rusjdi, Selfi Renita; Lestari, Yuniar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Vector control is still main effort to break the chain of transmission of Dengue Hemorrhagic Fever (DHF). Pyriproxyfen is recommended by WHO as an alternative insecticide because there are reports that Aedes sp mosquitoes Objective: This review is to determine the effectiveness of pyriproxyfen in controlling Aedes sp mosquito as a DHF vector. Methods: The research method used is a narrative review that explores primary literature on the effectiveness of pyriproxyfen in controlling Aedes sp mosquito as a dengue vector through research article databases. Literature was selected based on the inclusion and exclusion criteria specified. Literature review results were extracted and grouped according to the study's specific objectives: percentage of inhibition of emergence, percentage of larval mortality, and dose of pyriproxyfen used. Results: A total of eighteen pieces of literature include in this narrative review. Literature review results showed that effectiveness of pyriproxyfen against Aedes sp mosquitoes was in range of 80 – 100%, assessed from percentage Inhibition of Emergence (%IE). Highest reported percentage of larval mortality was 33.91% on a laboratory research scale. Doses used in a wide range of 0.005 μg/L – 1 mg/L (0.005 – 1000 ppb). Majority used dose of 0.01 mg/L (10 ppb) for third instar larvae target. Conclusion: Based on literature review results, pyriproxyfen effectively controls Aedes sp mosquito vectors on a laboratory scale to field conditions.